Application of Gratitude Counseling to Improve Psychological Well-Being in Adolescents of Kasih Murni Teladan Orphanage Medan - Wardani, Ni Kadek Su; Pristanti, Nindya Ayu; Simangunsong, Audri; Wulandari, Annastasya Sri; Abrory, M Amtsal; Cahya, Dita Dwi; Melinda, Rina (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2024)
This research aims to analyzes the Application of Gratitude Counseling to Improve Psychological Well Being in adolescents of Kasih Murni Teladan Orphanage Medan. This study uses a quantitative approach with the type of research method used, namely experimentation and uses a pre-experimental design research design to determine the effect of the research group before and after being given an intervention in the form of gratitude counseling to 10 adolescents with low levels of psychological well-being. The population in this study were 20 adolescents of the Kasih Murni Teladan Orphanage in Medan. The sampling technique in this study used purposive sampling so that a sample size of 10 adolescents with low levels of psychological well-being was obtained. Data collection techniques used in this study using questionnaires, observations and interviews. Data analysis uses parametric statistics through the t-test. Based on the results of the study, it was found that the average level of psychological well-being before being given the intervention was in the moderate and low categories but after being given the intervention it increased to the high category, thus there was a significant difference in the level of psychological well-being before and after being given the intervention.